Bioengineering liver microtissues for modeling non-alcoholic fatty liver disease - Negar Aasadollahei; Niloufar Rezaei; Reihaneh Golroo; Tarun Agarwal; Massoud Vosough; Abbas Piryaei (EXCLI journal, 2023)
Non-alcoholic fatty liver disease (NAFLD) has become the world’s most common chronic liver disease. However, due to the lack of reliable in vitro NAFLD models, drug development studies have faced many limitations, and there is no food and drug administration-approved medicine for NAFLD treatment. A functional biomimetic in vitro human liver model requires an optimized natural microenvironment using appropriate cellular composition, to provide constructive cell-cell interactions, and niche-specific bio-molecules to supply crucial cues as cell-matrix interplay. Such a suitable liver model could employ appropriate and desired biochemical, mechanical, and physical properties similar to native tissue. Moreover, bioengineered three-dimensional tissues, specially microtissues and organoids, and more recently using infusion-based cultivation systems such as microfluidics can mimic natural tissue conditions and facilitate the exchange of nutrients and soluble factors to improve physiological function in the in vitro generated constructs. This review highlights the key players involved in NAFLD initiation and progression and discussed the available cells and matrices for in vitro NAFLD modeling. The strategies for optimizing the liver microenvironment to generate a powerful and biomimetic in vitro NAFLD model were described as well. Finally, the current challenges and future perospective for promotion in this subject were discussed.